(untitled) (Journal of Research Updates in Polymer Science, 2020)
Fibres are preimpregnated by solutions of mono- and bis-maleimides with comonomers. Imides alone polymerize to resins with too low energies of fracture. In the presence of Methylene dianiline or Aniline Diphenylmethylenebismaleimide reacts via Michael addition to equimolar addition products. When fibres are preimpregnated with these addition compounds alone or in combination with flame retardants, B-prepregs are obtained, which after curing show high glass temperatures and sufficient energies of fracture. 2.5 moles of Diphenylmethylene bismaleimide and 1mol Methylene dianiline or 1mole Aniline react to resins with glass temperatures of 350 and 380°C and energies of fracture of 75 and 100J/m2. The resins contain no carcinogen or blood harming free amines. A one pot reaction starting from Methylene dianiline and Maleic anhydride is possible and more economic. As polymerized bismaleimides possess their imide bonds in the side chain, they are strictly spoken no polyimides with imide bonds in the main chain. Diphenylmethylenebismaleimide and styrene as copolymer react to an insoluble crosslinked polymer. Fibres are preimpregnated with equimolar mixtures of 2- Bromophenylmaleimide and styrene. After curing laminates with 285°C glass temperature and sufficient energies of fracture are obtained. The heat resistant resins are charring polymers and display higher Limiting Oxygen Indices, when the heats of combustion are increased. Differential Scanning Calorimetry determines the temperatures and the heats of glass transition, which indicate that the glass temperature is raised, when the enthalpy is increased and the entropy reduced, which is achievable by Diphenylbismaleimide and 2-Bromophenylmaleimide with their large side groups appropriate for intermolecular forces and steric hindrance.